Diel Transcriptional Oscillations of a Plastid Antiporter Reflect Increased Resilience of Thalassiosira pseudonana in Elevated CO2 - Valenzuela, Jacob J.; Ashworth, Justin; Cusick, Allison; Abbriano, Raffaela M.; Armbrust, E. Virginia; Hildebrand, Mark; Orellana, Mónica V.; Baliga, Nitin S. (Frontiers in Marine Science, 2021)
Acidification of the ocean due to high atmospheric CO2 levels may increase the resilience of diatoms causing dramatic shifts in abiotic and biotic cycles with lasting implications on marine ecosystems. Here, we report a potential bioindicator of a shift in the resilience of a coastal and centric model diatom Thalassiosira pseudonana under elevated CO2. Specifically, we have discovered, through EGFP-tagging, a plastid membrane localized putative Na+(K+)/H+ antiporter that is significantly upregulated at >800 ppm CO2, with a potentially important role in maintaining pH homeostasis. Notably, transcript abundance of this antiporter gene was relatively low and constant over the diel cycle under contemporary CO2 conditions. In future acidified oceanic conditions, dramatic oscillation with >10-fold change between nighttime (high) and daytime (low) transcript abundances of the antiporter was associated with increased resilience of T. pseudonana. By analyzing metatranscriptomic data from the Tara Oceans project, we demonstrate that phylogenetically diverse diatoms express homologs of this antiporter across the globe. We propose that the differential between night- and daytime transcript levels of the antiporter could serve as a bioindicator of a shift in the resilience of diatoms in response to high CO2 conditions in marine environments.